Bullying em escolares: fatores associados e sua relação com bruxismo e qualidade do sono - Bolsson, Gabriela Bohrer (2021)
The term bullying includes the practice of intentional and repeated acts of physical or psychological violence committed by one or more aggressors against a specific victim. Different factors have been related to the occurrence of bullying in childhood, including adverse oral health conditions. This thesis consists of two articles. The first assesses the ways in which oral health conditions and associated factors influence the occurrence of bullying in schoolchildren in the city of Santa Maria, Brazil. This cohort study began in 2010, with a random sample of 639 preschool children under 5 years of age. In the fourth stage of evaluating the sample components, 429 children aged between 11 and 15 years participated in the study again, totaling 10 years of follow-up. At this stage, to assess the occurrence of school bullying, the students answered the victimization scale of the Brazilian version of the Bullying Olweus Questionnaire (QBO). Oral health-related verbal bullying was assessed using a question contained in the Child Perception Questionnaire (CPQ11-14). Questions regarding demographic, socioeconomic and behavioral factors were assessed at baseline and were also obtained at follow-up through a structured questionnaire. In addition, study participants also answered questions regarding the sense of coherence (SDC). Assessments of oral conditions (dental caries, malocclusion and dental trauma) were performed at baseline and at follow-up through clinical examinations performed by calibrated examiners. As the main results of the first article, it was demonstrated that untreated dental caries and low socioeconomic status at baseline had direct and indirect impacts on the higher occurrence of dental bullying in the follow-up. In addition, SDC and oral health-related verbal bullying directly impacted the occurrence of more episodes of school bullying. The second article of this thesis is a cross-sectional study nested within the fourth phase (2020) of the previously mentioned cohort study, whose objective was to assess the impact of school and verbal bullying related to oral health on the occurrence of sleep bruxism and the quality of sleep of children. students in this sample. Information on clinical conditions, socioeconomic status and SDC were also considered in this study. Also, sleep bruxism and sleep quality were assessed through self-reports by students and guardians. It was found that individuals victims of school and verbal bullying related to oral health had a higher prevalence of sleep bruxism and sleep quality. High SDC students were protected from having sleep bruxism. In conclusion, the findings of this thesis demonstrated that tooth decay throughout childhood has a strong impact on the occurrence of school and verbal bullying related to oral health, and that these are associated with sleep bruxism and poor sleep quality. Our results also demonstrated that psychosocial factors, such as CDS, can play an important role in these relationships.